1987
DOI: 10.1016/0014-5793(87)80383-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of retinal transducin and phosphodiesterase activities by synthetic peptides of the phosphodiesterase γ‐subunit

Abstract: Synthetic peptides corresponding to various regions of the light‐activated guanosine 3′,5′‐cyclic monophosphate phosphodiesterase (PDE) γ‐subunit (PDEγ) from bovine retinal rod outer segments were synthesized and tested for their ability to inhibit PDE activity, and GTPase activity of transducin. One of these peptides, corresponding to PDEγ residues 31–45, inhibited PDE activity and GTPase activity in a dose‐dependent manner. The GTPase activity was inhibited by PDEγ‐3 non‐competitively. This region of the PDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…Such a high concentration of the peptide is needed for its phosphorylation because only a small amount of peptide may be in the correct conformation. A high concentration of the peptide was also required for inhibition of PDE (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a high concentration of the peptide is needed for its phosphorylation because only a small amount of peptide may be in the correct conformation. A high concentration of the peptide was also required for inhibition of PDE (16).…”
Section: Resultsmentioning
confidence: 99%
“…The cDNA sequence and corresponding amino acid sequences of bovine Py have been determined (21). A published report (16) has suggested that an active site of bovine Py for PDE inhibition is a region corresponding to residues 31-45, which is rich in lysine residues but contains only a single threonine and a single serine residue. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two functional regions in the ␥ subunit of PDE-6, a polycationic (amino acids 24 -46) and a C-terminal domain, interact with both transducin and PDE-6 catalytic subunits (31)(32)(33)(34). The C-terminal domain is essential for both the inhibitory action against PDE-6 (26, 31, 32, 35) and for stimulating transducin GTPase (36).…”
Section: Discussionmentioning
confidence: 99%
“…The PDE holoenzyme is tightly regulated by the Pγ inhibitory subunits. Much work has been done with bovine PDE to elucidate the important sites of interaction of Pγ with Pαβ [10][11][12][13][14][15][16][17][18][19][20][21]. It has been found that Pγ contains two distinct domains that interact with Pαβ : a central cationic region (residues approx.…”
Section: Introductionmentioning
confidence: 99%